Influence of Teacher Competence on Mathematics Performance in KCSE Examinations Among Public Schools in Nyatike Subcounty, Migori County Kenya - Ochieng, Kenaz Rakiro; Kiplagat, Paul; Nyongesa, Stephen (International Journal of Secondary Education, 2017)
Secondary school education provides a foundation for acquisition of further knowledge and skills in tertiary institutions of learning. It is a bed-rock where future productive human capital is nurtured to serve the dynamic needs of a nation’s labour market and the economy in general. Education is used to achieve more rapid economic, social, political, technological, scientific and cultural development in a country. In Kenyan education system, mathematics is a compulsory and an examinable subject offered at all levels of learning except for tertiary institutions where it is selective, yet requisite in some courses of study. There is much emphasis on mathematics performance examined nationally by the Kenya National Examinations Council (KNEC) hence necessitating the current study. As a matter of fact, students’ performance in mathematics has attracted attention from various stakeholders and further raised interest in teachers’ qualification in delivering the subject matter. This study ought to establish the influence of teacher competence on mathematics performance in KCSE examinations among public secondary schools in Nyatike Sub-county, Kenya. Teacher competence was conceptualized in terms of teacher educational qualification, teacher training and teacher experience and mathematics performance as the dependent variable. The study was based on three models namely; economical approach, stakeholder theory of management and humanistic-progressive model. The study used a descriptive research design with a survey method and targeted 50 public secondary schools. The researcher used structured questionnaires to collect data from the sampled respondents. The collected questionnaires were then analyzed using SPSS version 20. Both linear regression analysis and Pearson correlation analysis were used and the results presented in tables. The study findings revealed positive correlations between; teacher educational qualifications with mathematics performance, teacher training with mathematics performance, and teacher experience with mathematics performance. However, it was also noted that some teachers holding diplomas from reputable colleges such as Kenya Science University College perform better than those with undergraduate degrees from universities.
Keywords: Teacher Competence; Mathematics Performance; Qualification; Teacher Training; Teacher Experience